ASSESSING THE IMPACT OF TRAINING PROGRAMMES FOR DAIRY FARMERS BY KRISHI VIGYAN KENDRA, FARM SCIENCE CENTRE, INDIA - A. Jena. M. Chander; D. Bardhan (Journal of Animal and Plant Sciences, 2022)
India is spending huge amount of resources on agricultural training in general and animal husbandry training in specific but scanty research findings indicate actual impact of those training programmes and hardly any study accounted for selection bias while assessing impact of those training programmes. This study, therefore proposed to assess the impact of dairy farming trainings imparted during the duration of 2014-2016 by Krishi Vigyan Kendra (KVK) (Farm Science Centre) under ICAR- Indian Veterinary Research Institute (IVRI), Izatnagar, Uttar Pradesh, India. Data were collected from 80 trainee farmers and 240 non-trainee farmers on various aspects, i.e. their knowledge on scientific dairy husbandry practices, adoption of various scientific dairy husbandry practices in the field condition, attitude towards dairy farming, yield from dairy and profitability from scientific dairy farming. Logistic regression was applied to estimate the probability of participation in training programme. Propensity Score Matching (PSM) 1:1 was then used to control for the confounding variables which may affect the decision of trainees to participate in the training programme. Total of 76 matches were found and as such, the same number of trainee and non-trainee farmers were finally included in the study. The results revealed that the training programmes had significant impact on knowledge level on scientific dairy husbandry practices, better adoption of scientific animal husbandry practices and higher yield from dairy farming. Similarly, the trainings significantly and positively impacted on profitability from dairy farming. However, no significant impact of training on overall attitude of trainees towards scientific dairy farming was observed.
Keywords: Krishi Vigyan Kendra; Impact; Propensity Score Matching; Logistic regression